Internal jugular pressure increases during parabolic flight. Issue 24 (30th December 2016) - Martin, David S.; Lee, Stuart M. C.; Matz, Timothy P.; Westby, Christian M.; Scott, Jessica M.; Stenger, Michael B.; Platts, Steven H.
Abstract: One hypothesized contributor to vision changes experienced by >75% of International Space Station astronauts is elevated intracranial pressure (ICP). While no definitive data yet exist, elevated ICP might be secondary to the microgravity‐induced cephalad fluid shift, resulting in venous congestion (overfilling and distension) and inhibition of cerebrospinal and lymphatic fluid drainage from the skull. The objective of this study was to measure internal jugular venous pressure (IJVP) during normo‐ and hypo‐gravity as an index of venous congestion. IJVP was measured noninvasively using compression sonography at rest during end‐expiration in 11 normal, healthy subjects (3 M, 8 F) during normal gravity (1G; supine) and weightlessness (0G; seated) produced by parabolic flight. IJVP also was measured in two subjects during parabolas approximating Lunar (1/6G) and Martian gravity (1/3G). Finally, IJVP was measured during increased intrathoracic pressure produced using controlled Valsalva maneuvers. IJVP was higher in 0G than 1G (23.9 ± 5.6 vs. 9.9 ± 5.1 mmHg, mean ± SD P < 0.001) in all subjects, and IJVP increased as gravity levels decreased in two subjects. Finally, IJVP was greater in 0G than 1G at all expiration pressures ( P < 0.01). Taken together, these data suggest that IJVP is elevated during acute exposure to reduced gravity and may be elevated further by conditions that increase intrathoracic pressure, a strong modulator of central venous pressure and IJVP. However, whether elevated IJVP, and perhaps consequent venous congestion, observed during acute microgravity exposure contribute to vision changes during long‐duration spaceflight is yet to be determined. Abstract : Internal jugular venous pressure (IJVP) was evaluated noninvasively before, and during reduced gravity in parabolic flight. While in microgravity, IJVP was higher in all 11 subjects (23.9 ± 5.6 vs. 9.9 ± 5.1 mmHg, P < 0.001).